Evaluasi Strategis: Kebijakan Pertahanan Berbasis Geodefense dalam Menghadapi Ancaman Militer Kontemporer - Aris Sarjito (Program Studi Ilmu Pemerintahan, 2024)
Abstract This research explores the strategic evaluation of geodefense-based defense policies in addressing contemporary military threats within the evolving geopolitical landscape. Against the backdrop of increasing geopolitical tensions and diverse security challenges, this study aims to assess the effectiveness and efficiency of geodefense strategies in enhancing national security resilience. Utilizing qualitative research methods, secondary data from academic sources, government reports, and defense policy documents are analyzed to examine three main components: the geopolitical landscape and military threats, geodefense-based defense policies, and the development of a strategic evaluation framework. Findings reveal dynamic shifts in power dynamics, regional conflicts, and emerging security threats shaping the contemporary security environment. Geodefense-based defense policies are observed to prioritize strategic depth, geographic intelligence, and interagency coordination to mitigate security risks. Moreover, the development of a structured strategic evaluation framework facilitates comprehensive assessment and adaptation of defense strategies to evolving threats and challenges. This research underscores the importance of integrating geographic considerations, intelligence capabilities, and stakeholder collaboration in effective defense planning and strategy formulation.